Induction of SiHa Cells Apoptosis by Nanometer Realgar Suspension and Its Mechanism - 刘嵘 濮德敏 刘燕 程艳香 尹伶 李天 赵立波 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
The effects of nanometer realgar uterine cervix cancer cell line SiHa cells and suspension on proliferation and apoptosis of human oncogenic genes HPV16E6/E7 were investigated. A ＂micro-jet effiux＂ strategy was used for the preparation of nanometer realgar suspension. SiHa cells were treated with nanometer Realgar suspension in various concentrations （6.25, 12.5, 25 and 50 mg/L） for different durations （12, 24, 48 and 72 h）. The inhibitive effect of nanometer realgar suspension on growth of SiHa cells was detected by MTT method. Special morphological changes of apoptosis were observed by transmission electron microscopy （TEM） and DNA fragments electrophoresis. The apoptotic rate was quantified by flow cytometry （FCM）. The expression of HPV 16E6/E7 mRNA and protein was assayed by RT-PCR and Western blot respectively. The results showed after being treated with 25--50 mg/L nanometer realgar suspension for 48 h, the survival rate of SiHa cells was decreased, and apoptotic rate markedly increased in a time- and concentration-dependent manner. TEM and DNA electrophoresis revealed the special morphological changes of apoptosis. The apoptotic rate of SiHa cells treated with nanometer realgar suspension was significantly higher than in the control group （P〈0.01）, and G0/G1 phase arrest appeared following treatment with nanometer realgar suspension in 25 and 50 mg/L for 48 h. RT-PCR and Western blot assay indicated that nanometer realgar suspension reduced the HPV16E6/E7 gene expression. Nanometer realgar suspension could inhibit the proliferation and induce apoptosis of SiHa cells. The mechanism may be related to the down-regulation of the HPV16E6/E7 gene expression.